Pengembangan E-Modul SETS Berbasis Flipbook Maker Alternatif Pembelajaran Masa Pandemi Covid -19: Pengembangan E-Modul SETS Berbasis Flipbook Maker Alternatif Pembelajaran Masa Pandemi Covid -19 - Aulia Novitasari; Agnesya Dian Tiara (JURNAL BIOSHELL, 2022)
The outbreak of the corona virus requires all parties to be able to adapt to the industrial era 4.0, this revolution is marked by technological changes that have a strong influence on education, students and educators must be able to adapt to the digital learning process, on the other hand science learning must be in accordance with the nature of science, so that it requires a combination of digital media and approaches that can facilitate the development of the nature of science that has a positive impact on learning outcomes. The purpose of this research is to develop a flipbook maker-based SETS e-module that can be used on environmental pollution materials. This research is a type of R & D, with the ADDIE model development procedure consisting of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The feasibility test or the validity of the e-module was obtained through validation by two material experts, two language experts, and two media experts, the results obtained 94, 57% for material, 97.5% for language, and 96.53% for media with the acquisition of all three criteria very feasible. Practicality and attractiveness tests were obtained through the response test of educators and students, the results were 92.16% by students with very attractive criteria, and 97.6% by educators with very good criteria. Keywords: E- Modul, SETS, Flipbook Maker